Labor Market Need is Not Enough: A Normative Claim (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2025)
This article argues that labor market demand is an insufficient—and unstable—justification for expanding Prior Learning Assessment and Recognition (PLAR) for newcomers seeking entry into regulated professions. Drawing on PLAR’s “credit exchange” and “developmental” models and a Kantian ethical frame, it advances a normative claim that PLAR should be designed to benefit the person being assessed and that benefits to institutions, employers, or society must not come at the assessed individual’s expense. Using examples from Canadian provincial credential-recognition reforms, the paper shows how equity gains often occur only when shortages create political pressure, leaving newcomers vulnerable to renewed gatekeeping once demand shifts. The article concludes that PLAR policy and practice should be grounded explicitly in ethical commitments to fairness and non-harm, rather than relying primarily on human-capital or workforce rationales.Keywords: Prior learning assessment and recognition (PLAR); recognition of prior learning (RPL); normative ethics; internationally trained professionals; regulated professions; labor market policy; equity and fairness; credential recognition; Canada